Chemical composition and pharmacological properties of Flos sophorae immaturus, Flos sophorae and Fructus sophorae: a review - Ping Shi; Jiajun Liao; Ting Duan; Qingling Wu; Xiaoni Huang; Xiaodong Pei; Chenghua Wang (Journal of Future Foods, 2023)
The flower buds and fruits of Sophora japonica are known as Flos sophorae immaturus (Chinese Huaimi, FSI), Flos sophorae (Chinese Huaihua, FLS) and Fructus sophorae (Chinese Huaijiao, FRS) due to their different physiological forms. FSI and FLS are precious resources of homology of medicine and food, while FRS is a valuable Chinese herb, and all of which have been used for thousands of years. There are great differences in the active ingredients, functions and toxicological properties of FSI, FLS and FRS. However, they are often confused and assumed to have fairly similar validity, which is detrimental to their precision development of resources of homology of medicine and food. This review summarized the active constituents, analytical techniques and pharmacological properties of FSI, FLS and FRS, then systematically compared their differences. The article will help people better understand and distinguish the differences and characteristics of FSI, FLS and FRS in bioactive constituents, content of functional components and pharmacological properties, which can contribute to their highly efficient targeted applications in the future food and medical fields.